Meningkatkan Literasi dan Numerasi Berdasarkan Filsafat Ki Hadjar Dewantara di SDN Sumber Agung - Sriyono, Sriyono; Susanti, Rahmi; Yosef, Yosef; Nawawi, Effendi (Asian Journal of Early Childhood and Elementary Education, 2024)
The level of literacy and numeracy of students in Indonesia is still concerning, especially at the basic education level. At SDN Sumber Agung, which is in a rural environment, the challenge of improving literacy and numeracy is quite complex. Ki Hadjar Dewantara, an Indonesian education figure, has laid important foundations in the philosophy of national education. Ki Hadjar Dewantara's thinking emphasizes the importance of liberating education, namely education that can develop students' potential holistically, both in cognitive, affective, and psychomotor aspects. The purpose of this study is to analyze the application of Ki Hadjar Dewantara's philosophical values in improving literacy and numeracy at SDN Sumber Agung and identify effective learning strategies based on local wisdom. This study uses a qualitative approach with a case study method to explore the application of Ki Hadjar Dewantara's philosophical values in improving literacy and numeracy at SDN Sumber Agung. The results of this study show that the application of Ki Hadjar Dewantara's philosophical values at SDN Sumber Agung has succeeded in significantly improving students' literacy and numeracy skills. This is evidenced by the average score of students' literacy increased from 72 to 85 after one semester of applying methods based on local wisdom, such as the use of folklore in learning. Likewise in the numeracy aspect, the average score of students increased from 68 to 82 through contextual learning approaches, such as counting crops or using simple props.